The Influence of Trust and Convenience on Purchasing Decisions in Shopee E-commerce - Ningsih, Nonita Kristya; Yanti, Desma; Ony, Johan Gunady (Universitas Pamulang, 2024)
This study aims to determine the effect of trust and convenience on Shopee e-commerce purchasing decisions. The data used in this study are primary data. The population in this study are consumers who have shopped and used the Shopee application. The sample respondents were 115 respondents. The sampling technique is purposive sampling method. Primary data from this study were taken from questionnaires. The data analysis techniques used are validity test, reliability test, classical assumption test, which consists of normality test, multicollinearity test, and heteroscedasticity test, multiple regression analysis, hypothesis testing which consists of t test and coefficient of determination. The results in this study indicate that trust and convenience have a positive and significant effect on purchasing decisions in Shopee e-commerce.